Imaging diagnosis: chronic unilateral trigeminal neuropathy masquerading as a trigeminal peripheral nerve tumour on MRI in a dog. Issue 2 (25th November 2016) - Coia, Mark; Guevar, Julien; Penderis, Jacques; Hammond, Gawain
Abstract : A seven‐year‐old crossbred dog presented with chronic, progressive left unilateral masticatory muscle atrophy. The neurolocalisation was to the left mandibular branch of the trigeminal nerve. MRI identified thickening of the left trigeminal nerve root, which was isointense to grey matter on T1‐weighted and T2‐weighted images and displayed contrast enhancement. The masticatory muscles (temporalis muscle) ipsilateral to the trigeminal neuropathy (left‐sided) demonstrated contrast enhancement. Although a peripheral nerve sheath tumour was initially suspected, the lesion had largely resolved on repeated investigations after four months, supportive of a presumed diagnosis of trigeminal neuritis. Although unusual, unilateral trigeminal neuritis should be considered as a differential diagnosis, despite a progressive and chronic clinical course.